(3GdJLQjO GdUQjM dCMGOjK GdLGeY GdUMjMs - (3Rjf GdOjf CHj GdYHGS CMeO Rjf GdYGHOjf Hf YHO GddWja GdTQLj GdMfajs; (3GdGeGe eSde , CHh GdMSjf,J (B261 (3g` s
(3ChdgG (B:s
(3CeG HYO aGYde Cf cJGH GdLGeY GdUMjM ddEeGe GdcHjQ GdHNGQj QMeg Gddg JYGdi ef CYXe GdcJH GdeUfaI aj GdESdGe hCcKQgG ahGFO s
(3BNQgG (B:s
(3bGd GdfHi Udi Gddg Ydjg hSde cdeJGf MHjHJGf Edi GdQMef NajaJGf Ydi GddSGf KbjdJGf aj GdejRGf (B((3SHMGf Gddg hHMeOg SHMGf Gddg GdYXje(B) (3Je GdcJGH s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B221 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B232s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B554s
Keywords: (3GdMOjK h GdeUWdMs